Teachers and educational pact: an urgent issue - Roberto Sanz Ponce; Aurelio González Bertolín; Elena López Luján (Universidad de La Rioja, 2020)
The teacher is, together with the students, the factor with the greatest impact on the quality of the education system. But in the face of the forcefulness of this statement, there has been, in recent years, a gradual decrease in the decision-making capacity and influence of teachers on issues that affect the Educational System and its pedagogical implementation. Educational policies aimed at uniformity and standardization, accountability and bureaucratization undermine teachers' passion to teach. Therefore, the objective of this work is to analyze the role of the teacher in today's society, unravel the different trends and educational policies that diminish their decision-making and influence capacity and, later, describe a series of measures that revalue the teacher's role, Social and pedagogical. And for this, we advocate the need for an educational pact for the teaching profession. Among the measures presented are: the review of the processes of training and selection of teachers; the empowerment of "decision capital" and of autonomy among teachers; the elaboration of a Statute of the teaching profession; the creation of a professional career; and the dignification of the work of teachers.